Government Contingent Liabilities and the Measurement of Fiscal Impact. (IMF Working Papers; Working Paper, 1990)
Conventional fiscal accounting methodologies do not appropriately account for governments' noncash policies, such as their contingent liabilities. When these liabilities are called, budget costs can be large, as evidenced by the United States' saving and loan crisis. In general, deficit measures may underestimate the macroeconomic impact of government policies, promoting the substitution of noncash for cash expenditure and increasing future financing requirements. The paper describes extended deficit measures to address the problem, but notes their limited practical value. Nonetheless, some alternative methods of valuing contingent liabilities are proposed to gauge fiscal impact and facilitate budgetary control.